Single-cell analysis of the methanogenic archaeon Methanosarcina soligelidi from Siberian permafrost by means of confocal Raman microspectrocopy for astrobiological research - Serrano, S.; Wagner, D.; Böttger, Ute; de Vera, Jean Pierre Paul; Lasch, P.; Hermelink, A. (Planetary and Space Science, 2013)
Methanogenic archaea from Siberian permafrost are suitable model organisms that meet many of the preconditions for survival on the martian subsurface. These microorganisms have proven to be highly resistant when exposed to diverse stress factors such as desiccation, radiation and other thermo-physical martian conditions. In addition, methanogenic archaea produce methane as a metabolic byproduct, which was reported to be present in some regions of the Red Planet. The ExoMars mission will deploy a rover carrying a Raman spectrometer among the analytical instruments in order to search for signatures of life and to investigate the martian geochemistry. Raman spectroscopy is known as a powerful nondestructive optical technique for biosignature detection that requires only little sample preparation. In this study, we describe the use of confocal Raman microspectroscopy (CRM) as a rapid and sensitive technique for characterization of the methanogenic archaeon Methanosarcina soligelidi SMA-21 at the single cell level. These studies involved acquisition of Raman spectra from individual cells isolated from microbial cultures at different stages of growth. Spectral analyses indicated a high degree of heterogeneity between cells of individual cultures and also demonstrated the existence of growth-phase specific Raman patterns. For example, besides common Raman patterns of microbial cells, CRM additionally revealed the presence of lipid vesicles and CaCO3 particles in microbial preparations of M. soligelidi SMA-21, a finding that could be confirmed by electron microscopy. The results of this study suggest that heterogeneity and diversity of microorganisms have to be considered when using Raman-based technologies in future space exploration missions.